AL-QAWĀ‘ID AL-FIQHĪYAH: Tantangan Ilmiah Kemunculannya dan Aplikasinya dalam Bidang Ekonomi Sharī‘ah - Devid Frastiawan; Amir Sup (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2021)
This study aims to describe the background and scientific challenges of the birth of al-qawa>’id al-fiqhi<yah, the functions and benefits of al-qawa>’id al-fiqhi<yah, as well as the function, sound, meaning, intent, and application of the five basic rules (al-qawa>’id al-khams). The method used is qualitative-literature-descriptive. The results obtained are that there are three periods of compiling al-qawa>’id al-fiqhi<yah, namely the period of birth, growth-bookkeeping, and refinement. The scientific background and challenge of the birth of al-qawa>’id al-fiqhi<yah is to group fiqh problems so that they can quickly respond to the problems of legal cases that are increasingly emerging. Al-qawa>’id al-fiqhi<yah has several functions, namely as a principle and purpose of law, as a kind of source of law, and as a global summary of all the details of fiqh. While the benefits are that it is easy to learn, memorize, and apply by anyone to know the many furu>’iyyah laws, to know the differences and similarities between one issue and another without feeling any contradictions, to help in knowing the legal status of various contemporary problems being faced, knowing the fundamental objectives of Islamic shari’ah, and studying al-qawa>’id al-fiqhi<yah is the same as studying the building blocks of the formation of fiqh law. The five basic rules (al-qawa>’id al-khams), are functioned by all scholars to refer all fiqh issues to the five main rules. These rules include, everything depends on the intention, belief cannot be eliminated by doubt, difficulties bring to ease, harm must be removed, and customs can be made (consideration) law. Keywords: al-Qawa>‘id al-Fiqhi<yah; al-Qawa>‘id al-Khams; Shari<‘ah Economic